2022
DOI: 10.1080/10717544.2022.2070299
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogels for localized chemotherapy of liver cancer: a possible strategy for improved and safe liver cancer treatment

Abstract: The systemic drug has historically been preferred for the treatment of the majority of pathological conditions, particularly liver cancer. Indeed, this mode of treatment is associated with adverse reactions, toxicity, off-target accumulation, and rapid hepatic and renal clearance. Numerous efforts have been made to design systemic therapeutic carriers to improve retention while decreasing side effects and clearance. Following systemic medication, local administration of therapeutic agents allows for higher ‘ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 152 publications
0
19
0
Order By: Relevance
“…Thermograms of samples were documented using a DSC (8500, Perkin Elmer, American Fork, UT, USA). Nitrogenous atmosphere (20 mL/min) was used to carry out the measurements at heating rate of 10 • C/min and temperature range of about 30-600 • C [53].…”
Section: Thermogravimetric Analysis (Tga) and Differential Scanning C...mentioning
confidence: 99%
“…Thermograms of samples were documented using a DSC (8500, Perkin Elmer, American Fork, UT, USA). Nitrogenous atmosphere (20 mL/min) was used to carry out the measurements at heating rate of 10 • C/min and temperature range of about 30-600 • C [53].…”
Section: Thermogravimetric Analysis (Tga) and Differential Scanning C...mentioning
confidence: 99%
“…These classifications include the bases of polymer composition (e.g., monopolymer, copolymer), physical structure (e.g., amorphous, crystalline, mixed), cross-linking (e.g., chemical, physical), physiological response (e.g., thermoresponsive, pH responsive, stimuli-responsive), and overall ionic charge (e.g., cation, anion, nonionic). These properties and hydrogel behavior can be tuned or modified throughout formulation to generate hydrogels with unique degradation rates and drug-releasing kinetics . Due to their high stability and water content, many different classes of drugs can be incorporated within these polymeric systems such as anticancer immunotherapies (e.g., antibodies, cell-based therapies) as well as other bioactive agents.…”
Section: Hydrogelsmentioning
confidence: 99%
“…These properties and hydrogel behavior can be tuned or modified throughout formulation to generate hydrogels with unique degradation rates and drugreleasing kinetics. 91 Due to their high stability and water content, many different classes of drugs can be incorporated within these polymeric systems such as anticancer immunotherapies (e.g., antibodies, cell-based therapies) as well as other bioactive agents. It is critical to determine the physicochemical properties of the localized drug delivery system that will be suitable for effective loading and delivery of cargo, which is in part governed by the synthesis methods.…”
Section: ■ Hydrogelsmentioning
confidence: 99%
“…From recent studies, it was confirmed that Cabozantinib specifically targets endothelial growth factor receptor types 1 (VEGFR-1) ( 6 ), endothelial growth factor receptor types 2 (VEGFR-2) ( 7 ), FMS-like tyrosine kinase 3 (FLT-3) ( 8 ); which ultimately results in the demotion of angiogenesis and proliferation of malignant tumour ( 9 , 10 ). As far as liver cancer is concerned ( 11 ), it is the sixth most frequently recognized cancer and the fourth leading cause of cancer mortality across the globe ( 12 , 13 ). As per the WHO report, nearly 782,000 deaths have been recorded due to liver cancer, and surprisingly, liver cancer is more common in men than in women.…”
Section: Introductionmentioning
confidence: 99%